Helping children cope with a mother's breast cancer diagnosis: 'The telling box' - A pilot study - Joyce M.J. de Vos-Houben; Femke Bruls; Christel Heiyerjans; Rianne Roijen; Trijntje Völlink; Esther C. Bakker (Elsevier, 2024)
Objective: Discussing cancer with children presents challenges. Evidence underscores the importance of transparent communication in aiding children's coping mechanisms amidst a parent's diagnosis. 'The telling box' intervention was developed to assist mothers in discussing cancer with their children. This study aimed to explore nurses' and mothers' perspectives on the 'telling box'. Methods: Semi-structured interviews were conducted with six oncology nurses and five mothers diagnosed with breast cancer to assess their experiences and opinions regarding 'the telling box'. Results and conclusion: Both nurses and mothers emphasize the significance of open communication with children. Nurses identified 'the telling box' as a valuable resource for starting discussions about cancer with children, but lack of time and knowledge were factors preventing them from distributing the boxes. The current design of the box did not meet the mothers' needs, and the timing of its distribution was suboptimal. We recommend education of nurses on the use of 'the telling box' and customizing its content based on the child's age and treatment stage of the mother. Innovation: This study offers important insights from both patients and healthcare professionals. 'The telling box' was developed through collaborative efforts involving healthcare professionals and patients.